Prinsip 5C Sebagai Instrumen Utama dalam Analisis Pembiayaan (Studi Kasus di Koperasi Jasa Keuangan Syariah Baitul Mal Wat-Tamwil Nuansa Umat Cabang Ngoro) - Muhammad Ma'rur (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
Credit Risk Management for Banks and other Financial Institutions is very important, especially in providing loans or financing to customers. To reduce the occurrence of credit risk in the form of default, banks and other financial institutions should apply the 5C of principle. This  principle consist of; character, capacity, capital, collateral, and condition of economy. One of the financial institutions that has implemented this principle is the KJKS BMT Cabang Ngoro . but the facts show that the level of credit risk that occurs at BMT is very high (reaching 10%). This condition brings problems that needs to be  analysed and to provide the solutions to overcome this obstacle. This research uses a qualitative method with a field approach. The research process begins by conducting interviews, observations and documentation of the primary data needed. Furthermore, researchers conducted data analysis by reducing to make a working hypothesis. The results of this study can be concluded that the implementation of 5C principle in the financing assessment cannot be carried out to the the maximum level, therefore has brought  an impact on high defaults. Financial default  problems in BMT NU can be classified into two factors: a. Internal factors, namely the lack of professionalism of BMT managers. This cannot be separated from the problem of the lack of employee experience and the minimal number of BMT management members. In addition, the lack of clarity on NU's BMT towards non-collateral loan collections also contributed to this situation. b. external factors, namely factors of the customer itself. Because in some cases it can be seen that there are customers who are able to fulfill their obligations but are reluctant to pay, or even run away.To overcome this problem, the Central NU BMT must pay more attention and provide additional officers who have work experience, bearing in mind that all officers in the BMT ngoro branch are new employees. Keyword: Character, Collateral, Capital, BMT, Credit Risk, 5C’s of financial Management